2023
DOI: 10.1186/s12909-023-04200-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of flipped classroom based on CDIO concept combined with mini-CEX evaluation model in the clinical teaching of orthopedic nursing

Abstract: Background After the COVID-19 epidemic, the state has paid more attention to the clinical teaching function of affiliated hospitals of colleges and universities. Strengthening the integration of medicine and education and improving the quality and effect of clinical practice teaching are critical challenges facing medical education. The difficulty of orthopedic teaching lies in the characteristics of a wide variety of diseases, strong professionalism, and relatively abstract characteristics, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The study confirms that the flipped classroom method improves understanding and consolidates knowledge, increases motivation, and promotes the development of skills such as planning, organization, and information sharing, thus promoting a higher level of learning in students (Alharbi, 2022). Also, it has been confirmed that, as stated by Su et al (2023), the flipped classroom, as a teaching strategy, involves students accessing learning materials before class, researching independently on a specific platform, performing tasks in collaborative groups, and receiving individual guidance and support from teachers during class.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The study confirms that the flipped classroom method improves understanding and consolidates knowledge, increases motivation, and promotes the development of skills such as planning, organization, and information sharing, thus promoting a higher level of learning in students (Alharbi, 2022). Also, it has been confirmed that, as stated by Su et al (2023), the flipped classroom, as a teaching strategy, involves students accessing learning materials before class, researching independently on a specific platform, performing tasks in collaborative groups, and receiving individual guidance and support from teachers during class.…”
Section: Discussionsupporting
confidence: 72%
“…Within motivation, Lai et al (2021) emphasize the importance of active awareness, value awareness, self-responsibility, and selfefficacy. These aspects reflect the active search for knowledge, the connection of learning with personal reality, confidence in completing tasks, and the ability to attribute either success or failure to self-effort (Su et al, 2023;Ni, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the “Operate” phase, the study of actual cases further transforms arrhythmia theoretical knowledge into practical applications. Numerous studies underscore the efficacy of the CDIO framework in nursing education, particularly its role in enhancements in the understanding and application of knowledge [ 23 , 24 , 37 , 38 ]. A study on nursing students in orthopedic internships demonstrated that the CDIO model significantly enhances clinical competencies, analytical thinking, and self-directed learning by effectively integrating theoretical understanding with practical skills, thereby enriching problem-solving abilities and teaching effectiveness [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the CDIO model has gradually gained wider application within the nursing education system. Instructors utilize the CDIO model in various nursing student training programs, such as cardiovascular health behavior modification, orthopedic nursing, and the cultivation of core competencies [ 23 – 25 ]. Xinyang Su et al found that the CDIO model can stimulate the independent learning and critical thinking abilities of nursing interns, promote the organic integration of theory and practice in orthopedic nursing [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation